Preparation method of sodium ion battery soft and hard carbon composite material

CN122940146APending Publication Date: 2026-10-20LIAONING STARRY SKY SODIUM BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611071635.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种钠离子电池软硬碳复合材料的制备方法,具备在导电性、储钠容量和循环寿命方面均表现优异的优点,解决了现有制备成品无法同时兼顾高储钠容量、优良导电性与循环稳定性,难以满足高性能钠离子电池应用需求的问题

Benefits of technology

1、本发明的中温煤沥青经预氧化处理后形成的软碳组分具备类石墨结构,材料内部纵向堆叠有序度高,电子导电性显著增强,有效弥补了硬碳材料本征导电性不足的缺陷,而竹粉衍生的硬碳组分凭借无序碳层形成的纳米孔洞,为钠离子提供了充足的嵌入与脱出空间,保证了较高的储钠容量,在充放电过程中,软碳组分同时作为导电骨架,显著减少欧姆极化和电化学极化,显著提升材料的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of sodium-ion battery technology, and in particular to a method for preparing a soft and hard carbon composite material for sodium-ion batteries. The specific steps are as follows: S1, Pre-oxidation: Take 1-10g of coal tar pitch powder, heat it to 100-350℃ at room temperature for 50-200min and keep it at that temperature for 1-5 hours; S2, Take 1-10g of pre-oxidized coal tar pitch and 1-10g of bamboo powder, mix and ball mill them at a speed of 100-500 r / min for 1-5 hours; S3, Primary carbonization: Heat it to 600℃-800℃ at room temperature for 100-300min and keep it at that temperature for 1-3 hours; S4, Secondary carbonization: Heat it to 1000℃-1500℃ at room temperature for 200-400min and keep it at that temperature for 1-3 hours. This invention effectively compensates for the lack of intrinsic conductivity of hard carbon materials. The bamboo powder-derived hard carbon component provides ample space for sodium ions to insert and extract through the nanopores formed by the disordered carbon layer, ensuring a high sodium storage capacity. During charging and discharging, the soft carbon component also acts as a conductive framework, significantly reducing ohmic polarization and electrochemical polarization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, specifically to a method for preparing a soft and hard carbon composite material for sodium-ion batteries. Background Technology

[0002] Sodium-ion batteries, due to their abundant resources, low cost, and high safety, have shown broad application prospects in large-scale energy storage, low-speed electric vehicles, and smart grids. As a key component of sodium-ion batteries, the anode material directly affects the battery's capacity, rate performance, and cycle stability. Among existing anode material systems, hard carbon, with its disordered carbon layer structure and the resulting nanopores, can effectively accommodate the insertion and extraction of sodium ions, exhibiting high sodium storage capacity, good cycle stability, and excellent fast-charging performance. It has become the only commercially available anode material for sodium-ion batteries.

[0003] Currently, the mainstream industrialized traditional biomass hard carbon relies heavily on imported high-quality raw materials. Coal tar pitch carbon, which has advantages in localization, has a high yield and low price, but its direct carbonization products lack the nanoporous structure required for sodium storage, resulting in low sodium storage capacity. Bamboo-based biomass resources are renewable and abundant, but pure bamboo-based hard carbon has poor electronic conductivity, and its porous structure increases the electrode interface impedance, leading to poor rate performance and cycle life. Carbon materials prepared from single precursors all have performance shortcomings and cannot simultaneously achieve high sodium storage capacity, excellent conductivity, and cycle stability, making it difficult to meet the application requirements of high-performance sodium-ion batteries. To solve the above technical problems, we have designed a method for preparing soft and hard carbon composite materials for sodium-ion batteries. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0005] The purpose of this invention is to provide a method for preparing soft and hard carbon composite materials for sodium-ion batteries, which has the advantages of excellent conductivity, sodium storage capacity and cycle life. This solves the problem that existing finished products cannot simultaneously achieve high sodium storage capacity, excellent conductivity and cycle stability, and thus cannot meet the application requirements of high-performance sodium-ion batteries.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 1-10g of coal tar pitch powder, heat it to 100-350℃ at room temperature for 50-200min and keep it at that temperature for 1-5 hours; S2. Take 1-10g of pre-oxidized coal tar pitch and 1-10g of bamboo powder, mix and ball mill, and rotate at a speed of 100-500 r / min for 1-5 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃-800℃ and hold for 1-3 hours in 100-300 minutes; S4. Secondary carbonization: Increase the temperature from room temperature to 1000℃-1500℃ over 200-400 minutes and maintain it for 1-3 hours, then reduce it to 400℃-600℃ over 50-100 minutes to terminate the process; S5. Collect the sample and name it CTPZF-1.

[0007] Preferably, the coal tar pitch used is either high-temperature coal tar pitch or medium-temperature coal tar pitch.

[0008] Preferably, the bamboo powder raw material is one of the following: bamboo fern, moso bamboo, or white bamboo.

[0009] Preferably, in the pre-oxidation process of step S1, after the temperature is raised to the target temperature, a trace amount of oxygen is simultaneously introduced into the muffle furnace at a flow rate of 30-100 mL / min during the heat preservation stage, and the volume ratio of oxygen in the furnace atmosphere is controlled between 5% and 15%.

[0010] Preferably, in step S2, the raw material mixing and ball milling process uses a dry ball milling mode instead of a liquid phase ball milling mode. In dry ball milling, there is no need to add anhydrous ethanol medium. The pre-oxidized coal tar pitch and bamboo powder are directly put into the ball milling jar, and the ball-to-material ratio is controlled at 15:1-25:1. The mixture is ball milled at a speed of 200-400 r / min for 2-4 hours.

[0011] Preferably, both the primary carbonization in step S3 and the secondary carbonization in step S4 are carried out under an inert protective atmosphere, which is high-purity nitrogen gas with a flow rate of 50-200 mL / min.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The soft carbon component formed by the pre-oxidation treatment of medium-temperature coal tar pitch of the present invention has a graphite-like structure, with high vertical stacking order inside the material and significantly enhanced electronic conductivity, which effectively makes up for the defect of insufficient intrinsic conductivity of hard carbon materials. The bamboo powder-derived hard carbon component provides sufficient space for sodium ions to insert and extract through the nanopores formed by the disordered carbon layers, ensuring a high sodium storage capacity. During the charging and discharging process, the soft carbon component also acts as a conductive framework, significantly reducing ohmic polarization and electrochemical polarization, and significantly improving the cycle life of the material.

[0013] 2. This invention uses medium-temperature coal tar pitch and bamboo powder as raw materials, which are widely available and inexpensive. Compared with pure biomass-based hard carbon, it further reduces the production cost. The composite material exhibits excellent performance in terms of conductivity, sodium storage capacity and cycle life, and its overall performance is significantly improved. It is especially suitable for cost-sensitive large-scale energy storage applications.

[0014] 3. This invention adopts a dry ball milling process with a ball-to-material ratio and rotation speed, which eliminates the need to add ethanol liquid phase medium and removes the subsequent drying process. This avoids the problems of raw material component segregation and uneven mixing that occur during the liquid phase drying process, ensuring uniform compounding of the two phase raw materials. It also simplifies the preparation process, reduces process energy consumption and production costs, and improves the overall preparation efficiency and greenness of the process. Attached Figure Description

[0015] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0016] Figure 1 This is a cyclic diagram of CTPZF-1 / 3 of the present invention; Figure 2 This is a magnification chart of CTPZF-1 / 3 of the present invention; Figure 3 This is the XRD pattern of CTPZF-1 of the present invention. Detailed Implementation

[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Please see Figures 1-3 A method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 1-10g of coal tar pitch powder, heat it to 100-350℃ at room temperature for 50-200min and keep it at that temperature for 1-5 hours; S2. Take 1-10g of pre-oxidized coal tar pitch and 1-10g of bamboo powder, mix and ball mill, and rotate at a speed of 100-500 r / min for 1-5 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃-800℃ and hold for 1-3 hours in 100-300 minutes; S4. Secondary carbonization: Increase the temperature from room temperature to 1000℃-1500℃ over 200-400 minutes and maintain it for 1-3 hours, then reduce it to 400℃-600℃ over 50-100 minutes to terminate the process; S5. Collect the sample and name it CTPZF-1.

[0019] The coal tar pitch used is either high-temperature coal tar pitch or medium-temperature coal tar pitch. Both types of coal tar pitch are industrially mature, have abundant supply, low price, and stable carbon yield, which is suitable for large-scale production needs. At the same time, the thermal response characteristics of the two types of coal tar pitch are suitable for the pre-oxidation and segmented carbonization process of this invention, which can stably generate an ordered soft carbon conductive structure. The raw materials have strong versatility, effectively broadening the range of raw material selection and further improving the process adaptability and industrialization feasibility.

[0020] The bamboo powder raw material is one of the following: Phyllostachys edulis, Phyllostachys moso, and Phyllostachys aurea. Common bamboo raw materials such as Phyllostachys edulis, Phyllostachys moso, and Phyllostachys aurea are selected. The raw materials have a short growth cycle, are highly renewable, are readily available and inexpensive. Their natural fiber pore structure is excellent and can be stably inherited into the hard carbon component, ensuring sufficient sodium storage space and active sites in the composite material. At the same time, it realizes the localization of precursors, gets rid of dependence on imported biomass raw materials, stabilizes the supply chain, and avoids the risk of raw material price fluctuations.

[0021] In step S1, during the pre-oxidation process, after heating to the target temperature, a trace amount of oxygen is simultaneously introduced into the muffle furnace at a flow rate of 30-100 mL / min during the holding stage. The volume ratio of oxygen in the furnace atmosphere is controlled between 5% and 15%. The introduction of a trace amount of controllable oxygen and the limitation of the oxygen content ratio during the pre-oxidation stage can precisely control the type and number of oxygen-containing functional groups on the surface of coal tar pitch. The modified coal tar pitch can generate more closed microporous structures during the subsequent carbonization process, significantly increasing the active sites for sodium ion storage, improving the sodium storage capacity of the material, optimizing the interfacial characteristics of the soft carbon component, enhancing the interfacial bonding force between the soft and hard carbon phases, and further improving the structural integrity and electrochemical stability of the composite material.

[0022] In step S2, the raw material mixing and ball milling process uses a dry ball milling mode instead of a liquid phase ball milling. Dry ball milling does not require the addition of anhydrous ethanol as a medium. The pre-oxidized coal tar pitch and bamboo powder are directly placed into the ball milling jar, and the ball-to-material ratio is controlled at 15:1-25:1. The mixture is ball-milled at a speed of 200-400 r / min for 2-4 hours. The dry ball milling process with the ball-to-material ratio and speed eliminates the need for the addition of ethanol as a liquid phase medium, thus eliminating the need for subsequent drying. This process avoids the problems of raw material component segregation and uneven mixing that occur during the drying process in liquid phase, ensuring uniform compounding of the two phases of raw materials. It also simplifies the preparation process, reduces process energy consumption and production costs, and improves overall preparation efficiency and the greenness of the process.

[0023] Both the primary carbonization in step S3 and the secondary carbonization in step S4 are carried out under an inert protective atmosphere, which is high-purity nitrogen gas with a flow rate of 50-200 mL / min. The entire primary and secondary carbonization process is protected by high-purity nitrogen gas, which can isolate oxygen and water vapor in the high-temperature environment, effectively prevent carbon materials from oxidizing and burning and structural damage during high-temperature carbonization, and completely preserve the excellent microstructure and pore characteristics of soft and hard carbon, ensuring the stability of the material's electrical conductivity and sodium storage performance, and eliminating the electrochemical performance degradation caused by high-temperature defects.

[0024] Example 1 A method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 5g of coal tar pitch powder, heat it to 300℃ at room temperature for 90min and keep it at that temperature for 2h. S2. Take 3g of pre-oxidized coal tar pitch and 3g of bamboo powder, mix them and ball mill them at a speed of 400 r / min for 4 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃ in 120 minutes and hold for 2 hours; S4, Secondary carbonization: Increase the temperature from room temperature to 1300℃ in 260 minutes and hold for 2 hours, then reduce the temperature to 500℃ in 80 minutes to terminate the process; S5. Collect the sample and name it CTPZF-1.

[0025] Example 2 A method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 5g of coal tar pitch powder, heat it to 300℃ at room temperature for 90min and keep it at that temperature for 2h. S2. Take 1g of pre-oxidized coal tar pitch and 3g of bamboo powder, mix and ball mill, and rotate at 400 r / min for 4 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃ in 120 minutes and hold for 2 hours; S4, Secondary carbonization: Increase the temperature from room temperature to 1300℃ in 260 minutes and hold for 2 hours, then reduce the temperature to 500℃ in 80 minutes to terminate the process; S5. Collect the sample and name it CTPZF-1 / 3.

[0026] Example 3 A method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 5g of coal tar pitch powder, heat it to 300℃ at room temperature for 90min and keep it at that temperature for 2h. S2. Take 0.5g of pre-oxidized coal tar pitch and 3g of bamboo powder, mix and ball mill, and rotate at 400 r / min for 4 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃ in 120 minutes and hold for 2 hours; S4, Secondary carbonization: Increase the temperature from room temperature to 1300℃ in 260 minutes and hold for 2 hours, then reduce the temperature to 500℃ in 80 minutes to terminate the process; S5. Collect the sample and name it CTPZF-0.5 / 3.

[0027] Example 4 A method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 5g of coal tar pitch powder, heat it to 300℃ at room temperature for 90min and keep it at that temperature for 2h. S2. Take 3g of pre-oxidized coal tar pitch and 3g of bamboo powder, mix them and ball mill them at a speed of 400 r / min for 4 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃ in 120 minutes and hold for 2 hours; S4. Activation: Mix three times the weight of the sample with KOH, raise the temperature to 400℃ at room temperature for 125 min, hold for 1 h, then raise the temperature to 750℃ for 70 min, hold for 2 h, and then terminate the process. S5. Pour into 1M HCl and let stand for 12 hours. Wash and dry until neutral, then dry at 80℃ for 12 hours. S6. Secondary carbonization: Increase the temperature from room temperature to 1300℃ in 260 minutes and hold for 2 hours, then reduce the temperature to 500℃ in 80 minutes to terminate the process; S7. Collect the sample and name it CTPZF-1 activation.

[0028] It should be noted that any content not described in detail in this specification belongs to the prior art known to those skilled in the art. The specific embodiments described herein are merely illustrative examples of the spirit of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

Claims

1. A method for preparing a soft and hard carbon composite material for sodium-ion batteries, the specific steps of which are as follows: S1. Pre-oxidation: Take 1-10g of coal tar pitch powder, heat it to 100-350℃ at room temperature for 50-200min and keep it at that temperature for 1-5 hours; S2. Take 1-10g of pre-oxidized coal tar pitch and 1-10g of bamboo powder, mix and ball mill, and rotate at a speed of 100-500 r / min for 1-5 hours; S3, Primary carbonization: Increase the temperature from room temperature to 600℃-800℃ and hold for 1-3 hours in 100-300 minutes; S4. Secondary carbonization: Increase the temperature from room temperature to 1000℃-1500℃ over 200-400 minutes and maintain it for 1-3 hours, then reduce it to 400℃-600℃ over 50-100 minutes to terminate the process; S5. Collect the sample and name it CTPZF-1.

2. The method for preparing a soft and hard carbon composite material for sodium-ion batteries according to claim 1, characterized in that: The coal tar pitch used is either high-temperature coal tar pitch or medium-temperature coal tar pitch.

3. The method for preparing a soft and hard carbon composite material for sodium-ion batteries according to claim 1, characterized in that: The raw materials for bamboo powder are one of the following: Cizhu bamboo, Maozhu bamboo, and Baijia bamboo.

4. The method for preparing a soft and hard carbon composite material for sodium-ion batteries according to claim 1, characterized in that: In step S1, during the pre-oxidation process, after the temperature is raised to the target temperature, a trace amount of oxygen is simultaneously introduced into the muffle furnace at a flow rate of 30-100 mL / min during the holding stage. The volume ratio of oxygen in the furnace atmosphere is controlled between 5% and 15%.

5. The method for preparing a soft and hard carbon composite material for sodium-ion batteries according to claim 1, characterized in that: In step S2, the raw material mixing and ball milling process uses a dry ball milling mode instead of a liquid phase ball milling mode. In dry ball milling, there is no need to add anhydrous ethanol medium. The pre-oxidized coal tar pitch and bamboo powder are directly put into the ball milling jar, and the ball-to-material ratio is controlled at 15:1-25:

1. The ball milling is carried out at a speed of 200-400 r / min for 2-4 hours.

6. The method for preparing a soft and hard carbon composite material for sodium-ion batteries according to claim 1, characterized in that: Both the primary carbonization in step S3 and the secondary carbonization in step S4 are carried out under an inert protective atmosphere, which is high-purity nitrogen gas with a flow rate of 50-200 mL / min.